2021
DOI: 10.2166/wst.2021.222
|View full text |Cite
|
Sign up to set email alerts
|

Activated biochar derived from spentAuricularia auriculasubstrate for the efficient adsorption of cationic azo dyes from single and binary adsorptive systems

Abstract: In this study, spent Auricularia auricula substrate (AS)-derived biochar (ASBCs) and activated biochar with NaOH (A-ASBC) were evaluated for the adsorption of cationic azo dyes, including methylene blue (MB), rhodamine B (RB), and crystal violet (CV), from single and binary adsorptive systems. A-ASBC showed a higher maximum adsorption capacity for these dyes (MB: 53.62 mg·g−1, RB: 32.33 mg·g−1, CV: 735.73 mg·g−1) than ASBCs in a single system because it had a greater specific surface area and more oxygen conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…As the concentration increased, the adsorption sites tended to be saturated, and eventually adsorption capacity reach equilibrium. For the adsorption of MG and ST, the Freundlich model was more appropriate to describe the actual adsorption process ( Figure 7 a-d, Supplementary Table S3 ), suggesting that the adsorption of two dyes on GSBC and LSBC was nonuniform and multilayered ( Su et al, 2021 ). The 1/ n value were all between 0 and 1, indicative of the favorable adsorption for dyes onto both biochars ( Wang et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the concentration increased, the adsorption sites tended to be saturated, and eventually adsorption capacity reach equilibrium. For the adsorption of MG and ST, the Freundlich model was more appropriate to describe the actual adsorption process ( Figure 7 a-d, Supplementary Table S3 ), suggesting that the adsorption of two dyes on GSBC and LSBC was nonuniform and multilayered ( Su et al, 2021 ). The 1/ n value were all between 0 and 1, indicative of the favorable adsorption for dyes onto both biochars ( Wang et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the changes in pH before and after adsorption (Figures 4B,D,F,H), it was found that the final pH increased after dyes adsorption under acidic conditions, the possible reason is that the protonation of functional groups on biochar surface as well as the buffering effect of the inorganic elements in biochar (Su et al, 2021). When in Frontiers in Bioengineering and Biotechnology frontiersin.org alkaline solution, amounts of OH − were combined with the surface functional groups of biochar and involved in dyes adsorption, eventually causing the declined pH.…”
Section: Effect Of Phmentioning
confidence: 99%
“…Referring to Figure , the rice straw biosorbent follows the type II category. i.e., the adsorbent has both meso- and micropores on the surface . Micropores were observed in the first curve, and the mesopores’ presence was observed in the second curve concerning the relative pressure shown in Figure .…”
Section: Resultsmentioning
confidence: 93%
“…Additionally, the ease of their activation and modification allows for the significant development of their porous structure and functionalisation of the surface. Metal ions, synthetic dyes, phenols, amines or pharmaceuticals are commonly adsorbed on the biochars, activated biocarbons (products of physical and chemical activation of biomass) or different kinds of carbon-based nanocomposites [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. These materials are low-cost adsorbents and they can be easily regenerated.…”
Section: Introductionmentioning
confidence: 99%